Rheumatoid Arthritis, Circulating Inflammatory Proteins, and Hypertension: A Mendelian Randomization Study - Guobing Jia; Tao Guo; Lei Liu; Chengshi He (The Journal of Clinical Hypertension)
ABSTRACT Observational studies have indicated that there is an association between rheumatoid arthritis (RA) and an elevated risk of hypertension. However, a definitive causal relationship between the two conditions has not been established. The objective of this study was to investigate the causal link between RA and hypertension, as well as the potential mediating role of circulating inflammatory proteins in this relationship. We utilized Mendelian randomization (MR) to examine the causal relationship between RA and hypertension. The study data were obtained from publicly accessible genome‐wide association study (GWAS) databases and meta‐aggregates of large GWAS studies. The primary statistical method for determining causal effects was the inverse variance weighted (IVW) method, which was supplemented by a variety of sensitivity analyses. The results of the IVW method suggest a causal relationship between RA and an increased risk of hypertension (OR = 1.03, 95% CI = 1.01–1.04, p = 3.32 × 10−5). This association remained statistically significant even after adjusting for multiple confounding factors. Furthermore, MR analyses also revealed causal links between 10 circulating inflammatory proteins and the risk of hypertension, with TNF‐related activation‐induced cytokine partially mediating RA‐induced hypertension at a mediator ratio of 11.17% (0.27%–22.08%). Our study identifies causal relationships between several genetically determined inflammatory proteins and hypertension, establishing that RA increases hypertension risk, with inflammation partially mediating this effect. These findings provide new evidence supporting the inflammatory hypothesis in the mechanism of hypertension. Inflammatory factors may serve as potential targets for antihypertensive therapy.